Enhancing Students’ Understanding of Statistical Concepts through the Implementation of Lesson Study in Android-Assisted Learning - Anita Dewi Utami; Ramdhan Fazrianto Suwarman; Nur Ayufauziyah; Sinta Agustin Ningseh; Steve B Anapi (FKIP Universitas Lampung, 2026)
The integration of interactive digital media in mathematics learning has been widely recognized as an effective approach to enhancing students' conceptual understanding, particularly in statistics, a subject that demands both procedural fluency and meaningful data interpretation. Interactive media-assisted learning enables students to engage with abstract statistical concepts through visualization, simulation, and hands-on data manipulation, thereby fostering deeper comprehension and sustained motivation. Building on this premise, this study develops and implements a lesson study framework integrated with an Android-based application to improve junior high school students' understanding of statistical concepts. The lesson study method involved three cyclical stages: Plan, Do, and See. During the planning stage, the research team and collaborating mathematics teachers conducted a needs analysis, identified students' learning difficulties, developed discovery-learning-based instructional modules, and designed an Android application with data input, visualization, and statistical simulation capabilities. The implementation stage involved classroom instruction supported by the application, with systematic observation using a researcher-developed structured classroom observation protocol that covered student engagement, instructional alignment, and the quality of technology integration. The instrument was reviewed and validated by two experts in mathematics education before implementation. The reflection stage focused on collaborative evaluation of the learning process to iteratively refine instructional design and application functionality. Quantitative classroom observation data showed increased student participation and task completion across the implementation cycles. In addition, qualitative findings from classroom observations and reflective notes indicated improvements in students' conceptual understanding and classroom engagement. The integration of technology into the lesson study model fosters a more contextualized, interactive, and reflective learning environment, thereby enhancing the quality of statistics instruction at the junior high school level. Keywords: lesson study, Android application, statistics learning, student understanding, junior high school.